Assessing the Effectiveness of Monitoring Control and Surveillance of Illegal Fishing: The Case of West Africa - Doumbouya, Alkaly; Camara, Ousmane T.; Mamie, Josephus; Intchama, Jeremias F.; Jarra, Abdoulie; Ceesay, Salifu; Guèye, Assane; Ndiaye, Diène; Beibou, Ely; Padilla, Allan; Belhabib, Dyhia (Frontiers in Marine Science, 2017)
This paper assesses illegal fishing in West Africa, one of the regions most affected by Illegal, Unreported and Unregulated fishing (IUU) in the world. The catch, the economic loss and the amount recovered through Monitoring, Control and Surveillance (MCS) are calculated based on a reconstruction method, and the information made available through national MCS units, between 2010 and 2016 in an effort to assess the effectiveness of surveillance efforts in the region. Results show considerable loss of revenues for Mauritania, Senegal, The Gambia, Guinea Bissau, Guinea and Sierra Leone, estimated at 2.3 billion USD annually, while a minimal amount of 13 million USD is recovered through MCS. In addition, this paper finds that countries touched by the Ebola crisis (Guinea and Sierra Leone) drive a tremendous increase in the loss generated by illegal fishing. However, further analysis shows that the overall severity of illegal fishing, as defined by a range of types investigated here, declines as the fines against the most severe forms of IUU fishing increase. Finally this study finds that Sierra Leone and The Gambia have the highest scoring MCS systems, and were the countries where the most offenders are caught and charged with the highest fines, while Senegal’s new legislations which improved MCS during 2015 does not appear to show on the scoring results. This study finds that illegal fishing amounts the equivalent of 65% of the legal reported catch from West Africa and poses serious concern for food security, and the economy in the region.